2020
DOI: 10.1037/neu0000639
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve does not support the retrieval of well-known proper names in older people.

Abstract: Objective: To assess the role of cognitive reserve, age, gender and brain structure in proper name retrieval in advanced age. Method: Performance in 2 naming tasks (asking for proper names or common names) and 2 memory tasks was assessed. In separate hierarchical regressions, we evaluated whether retrieval was predicted by gray matter thickness or volume in selected structures (Model 1) and whether the addition of age and gender (Model 2) or of education (Model 3) explained significantly more variance. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…Education has been shown to have a differential effect on cognitive abilities in later life. For example, in a recent study with healthy older adults [19], we demonstrated that education positively affects the retrieval of common names and performance in memory tasks, while it does not influence the retrieval of famous proper names [see also 20]. Other studies have shown that older people with a higher education perform better than those with a lower education across different cognitive measures [15, 21].…”
Section: Introductionmentioning
confidence: 77%
“…Education has been shown to have a differential effect on cognitive abilities in later life. For example, in a recent study with healthy older adults [19], we demonstrated that education positively affects the retrieval of common names and performance in memory tasks, while it does not influence the retrieval of famous proper names [see also 20]. Other studies have shown that older people with a higher education perform better than those with a lower education across different cognitive measures [15, 21].…”
Section: Introductionmentioning
confidence: 77%
“…Importantly for the present study, evidence is recently emerging that a domain where CR does not seem to protect against age or pathology, is indeed the retrieval of PN as opposed to the retrieval of CN (Delazer et al, 2020;Mondini & Semenza, 2016;Montemurro et al, 2018Montemurro et al, , 2019. What is it that makes memory for PN less sensitive to CR than memory for CN?…”
Section: Introductionmentioning
confidence: 55%
“…Previous studies have shown that CR (estimated through education) can be associated with semantic abilities (Darby et al, 2017). In aging, the ability to retrieve PN and CN was related to the potential modulatory contribute of CR (Delazer et al, 2020;Montemurro et al, 2018Montemurro et al, , 2019 on cognition. Based on this premise, we investigated to what extent CR and semantic knowledge may be interconnected.…”
Section: Discussionmentioning
confidence: 92%
“…They found that older adults were particularly impaired in retrieving nondescriptive names, thus confirming that what makes PN fragile is their lack of descriptiveness. Consistent with the relation between semantic knowledge and CR, (Montemurro et al, 2018(Montemurro et al, , 2019 and (Delazer et al, 2020) showed how PN retrieval is weakly related to CR in aging, and suggested that this finding should be attributed to PN having poor semantic interconnections.…”
Section: Introductionmentioning
confidence: 71%
“…In the memory domain, relatively recent investigations have found another aspect of memory that seems weakly influenced by CR: memory for proper names (PN) as opposed to memory for common nouns (CN) (Margarete Delazer et al, 2020;Mondini & Semenza, 2016;Montemurro et al, 2018aMontemurro et al, , 2019a. What is it that makes memory for PN less sensitive to CR than memory for CN?…”
Section: Introductionmentioning
confidence: 99%